Supervisores de ensino da Rede Estadual de São Paulo: entre práticas e representações - Boldarine, Rosaria de Fátima [UNESP] (2014)
The present work had as objective to study the representations and practices of reading of the teaching supervisors of public schools that actuate in the city of São Paulo. What was intended to explore were the questions related to representations about the supervising action and about the practices of reading of the supervisors and how these representations and practices actuate in the supervising process, collaborating or not to the improvement of the processes of teaching and learning and with the melioration of the teaching formation. The choice of the subjects was related to the perspective that, although teaching supervisors are effective participants of questions regarding to the school, the pedagogical approach is not always turned, specifically, to them. For the development of the study, the methodology that, at first, subsidized the work searched for support in the sequenced triangulation, using questionnaires (232 questionnaires answered) and semi structured interviews (13 interviews) as instruments of data collection. Add to that, it was made a study of the documents that situate the actuation of the teaching supervisor. The results point to an indetermination of the role of the teaching supervisor, just like difficulties in balancing the administrative and pedagogical functions inherent to the supervising function in the state of São Paulo. In relation to the practices of reading, it was possible to evidence the reading mostly guided by the bibliography offered by the Government Department of Education of the state of São Paulo, what does not necessarily collaborate to the processes of formation of the teachers as well as the supervisors interviewed.